2011
DOI: 10.1016/j.jmbbm.2011.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Regional and fiber orientation dependent shear properties and anisotropy of bovine meniscus

Abstract: Imaging of meniscal tissue reveals an extracellular matrix comprised of collagen fibrils arranged in circumferential bundles and radially aligned tie fibers, implicating structural material anisotropy. Biochemical analyses demonstrate regional disparities of proteoglycan content throughout the meniscal body, a constituent known to affect the shearing response of fibrocartilagenous tissue. Despite this phenomenological evidence and previous mechanical testing implicating otherwise, the meniscus if often modeled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 39 publications
2
32
0
Order By: Relevance
“…6a,b). Consistent with previous reports on human [2] and bovine [41] menisci, collagen fibrils on the meniscal surface were oriented randomly within the transverse plane. In the interior, the fibrils were aligned along the fiber axis within each structural unit: circumferentially for circumferential fibers, and radially for superficial layer and radial tie fibers.…”
Section: Resultssupporting
confidence: 91%
“…6a,b). Consistent with previous reports on human [2] and bovine [41] menisci, collagen fibrils on the meniscal surface were oriented randomly within the transverse plane. In the interior, the fibrils were aligned along the fiber axis within each structural unit: circumferentially for circumferential fibers, and radially for superficial layer and radial tie fibers.…”
Section: Resultssupporting
confidence: 91%
“…Baro et al (2012) found that the contact modulus was significantly higher in the anterior region and lowest at the posterior region, supporting the result of the current study with highest properties in the anterior region. Shear modulus has also been reported in bovine meniscus at three anatomical locations (Abraham et al, 2011). Although not significantly different, the anterior region had a higher shear modulus than the central region.…”
Section: Discussionmentioning
confidence: 61%
“…An electric dermatome (D42, Humeca, Enschede, The Netherlands) was used to prepare full-thickness skin slices (thickness: 1.2-1.6 mm) from which square samples (8 Â 8 mm) were punched. The skin samples had an aspect ratio (thickness/width) of 1:6-1:5, which is close to the ratio of 1:4 recommended to reduce/minimise effects of strain concentrations at boundaries (Abraham et al, 2011;Horgan and Murphy, 2011). Pilot tests showed that the surface of the through thickness plane of the as-received skin did not present a unique, nonrepetitive high contrast pattern that is required for image correlation (Lecompte et al, 2006).…”
Section: Preparation and Preservation Of Skin Samplesmentioning
confidence: 71%